Spatial analysis of urban poverty from the social dimension in the areas of Rasht city - Alizadeh -; Mohammad Taghi Masoumi; Hossein Nazmfar; Akbar Abravesh (تحقیقات کاربردی علوم جغرافیایی)
Today, with the expansion of urbanization and the increase in the population of cities, urban poverty is one of the important problems that it seems necessary to fight. In the 21st century, one of the indicators of urban progress is the issue of low urban poverty (Lemanski and Marx, 2015). In order to analyze and evaluate the indicators of urban poverty in Rasht city in different blocks and to cluster social poverty in this city (very poor, poor, average, wealthy, very wealthy), to analyze social poverty and extract spatial hot spots from Arc software. Gis was used. And the extraction of different areas of the city was calculated from the R software and by the multi-indicator Prometheus decision-making method, where the weight of the indicators was obtained by the ANP method from the raw data of the statistical blocks of Rasht city in the census of 2015. The findings of the research showed that comparatively, the central parts of the city are covered by medium blocks, and in the outer and peripheral parts of the city center, two hot spot areas are observed, which contain very prosperous blocks. Cold spots are also clearly visible on the outer edge of the city and they cover very poor and poor blocks, and except for the hot and cold spots, the city is mostly in the form of mild spots and most of the blocks are in poor condition. They are placed in average social poverty. Also, based on the findings of the research, most of the deprived areas in terms of social poverty in Rasht city are located in the north-west and north-east parts of the city.